PENGGUNAAN ARANG AKTIF KULIT DURIAN (Durio zibethinus Murr) TERHADAP TINGKAT ADSORPSI KROMIUM (Cr6+) PADA LIMBAH BATIK - Moelyaningrum, Anita Dewi; Zarkasi, Kharta; Ningrum, Prehatin Trirahayu (Efektor, 2018)
Chromium (Cr6+) is a heavy metal that often finds in the batik wastewater. The activated carbon of durian peel (Durio zibethinus Murr.) Is an adsorbent which can adsorb heavy metals in the batik wastewater. The purpose of this study to analyze the effectiveness of the durian peel activated carbon to adsorb Cr6+ in the batik wastewater. This research was the true experiment with six repetitions. The sample consists of the control group (C) and the treatment groups (X1, X2, X3). Adsorption has done by using the mass of durian peel activated carbon 20 gr/litter (X1), 30 gr/ litter (X2), and 40 gr/ litter (X3). Each sample contacted with batik wastewater stirred by jar test with a speed of 400 rpm for one minute, then it allowed to stand 30 minutes. After that, the results compared with the control group. Data were analyzed by Kruskal-Wallis test and Mann-Whitney test. The results show that there was the difference between the control group and the treatment groups (p = 0.017). The most significant differences occurred in the third treatment group (X3) (p= 0.029).